The Protective Role of crude Polyphenolic Compounds Extracted from black Olive fruit (Oleaeuropae ) on Liver Functions in Males Rats Treated with Hydrogen Peroxide - Alol, Layla Hashim (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted to investigate the protective role of polyphenolic compounds extracted from olive (Oleaeuropae) to contrast the damaging effects of 1% hydrogen peroxide on liver functions in male rats. Crude polyphenolic compounds were extracted from fruits of black olive by 95% methanolic extraction method. Twenty adult male rats (200-220gm.) were randomly divided into four equals groups and treated daily for 30 days. Rats in the first group received tap water (orally)and considered as control group, animals of second group received 1% H2O2 in drinking water . The rats in the third group received 1% H2O2 in drinking water plus 200mg/kgB.W. of crude polyphenolic compounds while animals in the fourth group received 200mg/kg B.W. of crude polyphenoliccompounds. At the end of the experiment, blood samples were taken to investigate the activity of liver enzymes (Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT), concentration of total serum bilirubin, as well as protein picture of blood serum by using agarose gel electrophoresis. Ultimately, animals of all groups were sacrified to examine the histopathological changes in liver. The results illustrated significant increase (P<0.05) in liver enzymes activity (AST,ALT) and total serum bilirubin in H2O2 treated group as compared with control. Although rats treated polyphenolic compounds of olive plus H2O2 showed significant decrement (P<0.05) in ALT activity and total serum bilirubin, while no significant alteration in (AST) activity was recorded in H2O2 treated group. The result also demonstrated significant decrease (P<0.05) in authority of ALT, total serum bilirubin in animals treated with polyphenolic compounds. Serum proteins showed a significant (P<0.05) decreament of albumin percentage and increment of globulins in H2O2 treated group as well as polyphenolic compounds treated group as compared with control group (G1) . However, no significant different in group treated with polyphenolic compounds as compared with control. Histological sections of liver illustrated clear impact of group treated with H2O2, manifested by necrosis of hepatic cells with infiltration of inflammatory cells while animals treated with polyphenolic compounds plus H2O2 revealed slight infiltration of inflammatory cells with proliferation of kupffer cells in liver. In infereance, the autcomes of this study documented the advantageous effect of crude polyphenolic compounds of olive apposite the noxious effect of H2o2 on liver function of adult males rats.